2015
DOI: 10.1016/j.ajog.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Screening ultrasound as an adjunct to mammography in women with mammographically dense breasts

Abstract: There is increasing interest in the potential benefits and harms of screening ultrasound to supplement mammographic screening of women with dense breast tissue. We review the current evidence regarding adjunctive screening breast ultrasound (US) and provide a summary for clinicians who counsel patients with dense breasts. We conducted a comprehensive literature review of published clinical trials and observational cohort studies assessing the efficacy of screening handheld US (HHUS) and automated breast US (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 32 publications
1
88
0
3
Order By: Relevance
“…When mammography is combined with other screening techniques such as US or tomosynthesis, the cancer detection rates increase from 6.1/1000 using mammography alone (4.4% false-positive rate) to 8/1000 using mammography plus tomosynthesis (5.3% false-positive rate) and 11.8/1000 using mammography plus US (10.4% false-positive rate) in high-risk women (51,52). When US is used as an adjunctive screening technique to mammography, positive predictive values of as low as 5.6% were reported (53). These rates indicate that many women are called back for unnecessary biopsies, which leads to increased health care costs and psychological stress for women.…”
Section: Breast Cancermentioning
confidence: 99%
“…When mammography is combined with other screening techniques such as US or tomosynthesis, the cancer detection rates increase from 6.1/1000 using mammography alone (4.4% false-positive rate) to 8/1000 using mammography plus tomosynthesis (5.3% false-positive rate) and 11.8/1000 using mammography plus US (10.4% false-positive rate) in high-risk women (51,52). When US is used as an adjunctive screening technique to mammography, positive predictive values of as low as 5.6% were reported (53). These rates indicate that many women are called back for unnecessary biopsies, which leads to increased health care costs and psychological stress for women.…”
Section: Breast Cancermentioning
confidence: 99%
“…Increased MD also potentially lowers the sensitivity of mammography by obscuring small masses [4,5]. Accurate and reliable assessment of MD has crucial clinical significance, as women with high MD are often referred for additional magnetic resonance imaging (MRI) or ultrasound examinations in order to increase the likelihood of early breast cancer detection [6,7]. Up to now, 19 states of the USA have signed legislation requiring that women are told of their MD status when they attend mammographic breast examinations [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, opponents of 3D supine automated breast ultrasound may argue that previous ABUS and ABVS studies showed an average 10 percent lower detection rate, higher rate of false positives and higher recall rates compared to physician-performed whole breast HHUS (1,2,5). More shadowing artefacts created by angulated Cooper ligaments and fibrous structure, especially at the periphery of the breast are causing false positive cases and may need supplementary characterization to differentiate a pseudo lesion from a real lesion by use of HHUS, Doppler and elastographic techniques.…”
mentioning
confidence: 99%
“…Women with heterogeneous and extremely dense breast tissue show a 3-5 times higher relative risk than women with fatty breasts as referenced in meta-analysis, but only a 2 times higher relative risk than women with scattered fibroglandular tissue (18). Recommendations to overcome masking in women with dense breasts focus on MRI, ultrasound and, more recently digital tomosynthesis (2,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation